ASSESSMENT OF CHEMISTRY TEACHERS’ AWARENESS OF OBJECTIVE AND CONTENT COVERAGE OF THE CHEMISTRY CURRICULUM IN SECONDARY SCHOOLS IN NORTH CENTRAL NIGERIA - Nagenu, Safiya Umar; Dajal, R G; Apochi, M A (International Journal of Allied Sciences (IJAS), 2025)
The study investigated the level of awareness of the objectives and content coverage of the Chemistry Curriculum by Chemistry teachers based on location. The descriptive survey research design was adopted and Chemistry teachers in Senior Secondary Schools in North Central Nigeria were employed. The population of the study was two thousand and forty-eight Chemistry teachers from three out of the six North Central States. The three selected states are Benue, Nasarawa and Niger. The sample size was 264 Chemistry teachers from the randomly selected schools for the study. The Chemistry Curriculum Implementation Questionnaire was used to determine the level of curriculum awareness objectives. The research hypotheses were tested using independent t-test statistics at alpha 0.05 level of significance. It was revealed that there was no significant difference in the level of awareness of the objectives of the Chemistry Curriculum irrespective of gender and location in Senior Secondary Schools in North Central Nigeria. It was recommended that teachers should be retrained through workshops and seminars on the objectives of the Chemistry Curriculum and teachers should always be part of curriculum planning for appropriate implementation of the Chemistry Curriculum among others.